Pengaruh Motivasi Dan Pelatihan Terhadap Kompetensi Pada Karyawan Tetap PT Asuransi Jasaraharja Putera Kantor Pusat - Habsulhadiprasodjo Nurhadi; Budiyanto Budiyanto (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This study aims to analyze the effect of recruitment and selection on employee competence at PT Asuransi Jasaraharja Putera Head Office). The population of this study are permanent employees of PT Asuransi Jasaraharja Putera head office as many as 150 people. The sample used was calculated using the Slovin formula and produced as many as 60 respondents. The data analysis technique used in this study is multiple linear regression analysis with the help of SPSS 24 software. Hasl research shows that motivation is partially positive and significant effect on employee competence with a significance value of 0.002 and a beta coefficient of 0.208. Partial training has a positive and significant effect on employee competence with a significance value of 0.000 and a beta coefficient of 0.626. Motivation and training simultaneously have a positive and significant effect with a significance value of 0.000 and a beta coefficient value of 0.834 on employee competence.